The effect of mindfulness-based nursing support on the psychosocial status of women receiving infertility treatment: a randomized controlled trial - Özen İnam; İlkay Güngör Satılmış (BMC Women's Health)
Abstract Background This study aimed to evaluate the effect of mindfulness-based support on the psychosocial status of women undergoing infertility treatment. Method The study was conducted with 34 women who were about to start in vitro fertilization (IVF) and met the inclusion criteria. Participants were randomly assigned to either the experimental group (n = 17) or the control group (n = 17) using random number sequences generated on “ http://www.random.org . This process accounted for potential participant loss and was implemented in the order of participation. When cases withdrew, new participants were assigned based on the random sequence. All participants were women over the age of 18, literate, and users of smartphones. The experimental group used the IVFmind mobile application, specially developed for this study to facilitate mindfulness practices for infertility treatment. Psychosocial status was assessed using the Mindfulness Attention Awareness Scale, Infertility Self-Efficacy Scale-Short Form, Infertility Adjustment Scale, and Depression Anxiety Stress Scale. Data were collected through pre-tests and post-tests, and statistical analyses were performed. Results There were no significant differences between the experimental and control groups in terms of socio-demographic characteristics and infertility-related factors (p > 0.05). Mindfulness Attention Awareness Scale: No significant difference was found between groups in the pre-test scores (U = 120,000, p = 0.398). However, post-test scores of the experimental group were significantly higher than those of the control group (U = 0.000, p < 0.001). Infertility Self-Efficacy Scale-Short Form: No significant difference was found between groups in the pre-test scores (U = 125,500, p = 0.503). In the post-test, the experimental group scored significantly higher than the control group (U = 0.000, p < 0.001). Infertility Adjustment Scale: Pre-test scores showed no significant differences between the groups (U = 106,500, p = 0.184). In the post-test, the experimental group had significantly lower scores compared to the control group, indicating better adjustment (U = 3,000, p < 0.001). Depression Anxiety Stress Scale: There was no significant difference between the groups in the pre-test scores (U = 141,000, p = 0.904). However, post-test scores of the experimental group were significantly lower than those of the control group (U = 56,500, p = 0.002). Conclusions The mindfulness-based mobile application positively impacted the psychosocial status of women undergoing infertility treatment, demonstrating significant improvements. The experimental group showed notable increases in mindfulness, self-efficacy, and adjustment levels, along with significant reductions in depression and anxiety. These results highlight the effectiveness of mindfulness-based interventions in addressing psychological challenges associated with infertility and suggest that mobile applications can be a valuable tool for supporting mental health in this context. Trial registration The research was registered on http://clinicaltrials.gov (ID: NCT05708937). Date of Registration: 01\24\2023.